Etnomatematika: Menumbuhkan Kemampuan Berpikir Kritis Melalui Budaya Dan Matematika - Adhetia Martyanti; Suhartini Suhartini (IndoMath: Indonesia Mathematics Education, 2018)
The critical thinking skill is one of the skills that students need to have in the present century. However, this skill is not fully owned by students. This article aims to describe the mathematics learning activities based on ethnomatematics in relation to foster students' critical thinking skill. The method used in this research is research of library research (library research). The data in this study is secondary data in the form of research results such as scientific books, scientific journals, research reports, and other relevant sources. Data analysis techniques used in the study include three stages: organize, synthesize, and identify. The results of literature studies show that by selecting appropriate cultural content, ethnomatmatic-based mathematics learning has relevance to indicators on critical thinking skills, which include interpretation, analysis, evaluation, and decision making. Thus, the learning of mathematics based on ethnomatematics can be used as one of mathematics learning alternative to develop students' critical thinking ability.